2003
DOI: 10.1074/jbc.m308808200
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase-type Plasminogen Activator Receptor Inhibits Cancer Cell Growth and Invasion by Direct Urokinase-independent Effects on Cell Signaling

Abstract: The urokinase-type plasminogen activator receptor (uPAR) is released from human cancers and is readily detected in blood. In animal models, soluble uPAR (Su-PAR) antagonizes cancer progression; however, the mechanism by which SuPAR functions in vivo remains unclear. It is generally thought that SuPAR scavenges uPA and prevents its interaction with membrane-anchored uPAR. In this study, we demonstrate a novel molecular mechanism by which SuPAR may inhibit cancer progression. We show that SuPAR has the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 66 publications
4
49
0
Order By: Relevance
“…In support of this hypothesis, soluble uPAR has been shown to activate cell signaling similarly to uPA (15)(16)(17)(18). Furthermore, multiple signaling receptors have been co-immunoprecipitated or co-localized with cell surface uPAR, including integrins, FPR-like receptor-1/lipoxin A4 receptor (FPRL-1), and the EGFR (7,13,19,20).…”
mentioning
confidence: 76%
“…In support of this hypothesis, soluble uPAR has been shown to activate cell signaling similarly to uPA (15)(16)(17)(18). Furthermore, multiple signaling receptors have been co-immunoprecipitated or co-localized with cell surface uPAR, including integrins, FPR-like receptor-1/lipoxin A4 receptor (FPRL-1), and the EGFR (7,13,19,20).…”
mentioning
confidence: 76%
“…We previously demonstrated that suPAR may function as a cell signaling agonist or antagonist depending on whether membrane-anchored uPAR in the target cell is actively engaged in cell signaling (27). The basal state of activation of signaling factors such as ERK1/2 in the target cell also is important (27).…”
Section: Discussionmentioning
confidence: 99%
“…The basal state of activation of signaling factors such as ERK1/2 in the target cell also is important (27). suPAR may compete with membrane-anchored uPAR for coreceptors such as FPRL-1 (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is precedent for soluble forms of cellular receptors as direct regulators of cell physiology. The soluble form of the urokinase receptor, uPAR, regulates activation of ERK/MAPK and thereby controls cell growth and cell migration (66).…”
Section: Figurementioning
confidence: 99%